2005
DOI: 10.1152/ajpheart.00797.2004
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol ingestion before burn injury decreases splanchnic blood flow and oxygen delivery

Abstract: . Alcohol ingestion before burn injury decreases splanchnic blood flow and oxygen delivery. Am J Physiol Heart Circ Physiol 288: H716 -H721, 2005. First published September 23, 2004; doi:10.1152/ajpheart.00797.2004.-Recent studies from our laboratory have shown that alcohol and burn injury impair intestinal barrier and immune functions. Although multiple factors can contribute to impaired intestinal barrier function, such an alteration could result from a decrease in intestinal blood flow (BF) and oxygen deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
6
14
0
Order By: Relevance
“…This notion is supported by lack of changes in vascular NOS in ethanol fed rats (data not shown). On the other hand, reported studies including ours have established a role for reduced cardiac output, stroke volume, and myocardial contractility in the acute hypotensive effect of ethanol in female rats (El-Mas and Abdel-Rahman, 1999a, b; Choudhry et al, 2005); these findings conform with the reported depressant effect of ethanol on cardiac function (Kelbaek, 1990). Therefore, we tested the hypothesis that alterations in cardiac dynamics (myocardial contractility and autonomic activity) might underlie the hypotensive action of chronic ethanol in female rats.…”
Section: Discussionsupporting
confidence: 89%
“…This notion is supported by lack of changes in vascular NOS in ethanol fed rats (data not shown). On the other hand, reported studies including ours have established a role for reduced cardiac output, stroke volume, and myocardial contractility in the acute hypotensive effect of ethanol in female rats (El-Mas and Abdel-Rahman, 1999a, b; Choudhry et al, 2005); these findings conform with the reported depressant effect of ethanol on cardiac function (Kelbaek, 1990). Therefore, we tested the hypothesis that alterations in cardiac dynamics (myocardial contractility and autonomic activity) might underlie the hypotensive action of chronic ethanol in female rats.…”
Section: Discussionsupporting
confidence: 89%
“…Based on this temporal relationship between BP and 1dP/dt max , it is conceivable to assume that the reduced myocardial contractility might be responsible, at least in part, for the hypotensive action of 5% ethanol. The present demonstration of reduced myocardial contractility in ethanol-fed SHRs is consistent with the reported depressant effect of ethanol on cardiac function (Child et al, 1979;Kelbaek et al, 1985), and the established role of reduced cardiac output and stroke volume associated with ethanol-evoked hypotension in other rat models (Choudhry et al, 2005;Abdel-Rahman, 1999a, 1999b). In contrast, modulation of myocardial contractility does not appear to contribute to the hypotensive effect of 2.5% ethanol as 1dP/dt max remained unaltered in these rats.…”
Section: Discussionsupporting
confidence: 89%
“…The radiotelemetry technique adopted in the present study allowed the computation of the maximum rate of pressure rise across the BP waveform (1dP/dt max ), which serves as an index of myocardial contractility (Mehta et al, 1998;van den Buuse, 2003). Reported findings concerning the effect of ethanol on myocardial contractility are quite variable and depend on the animal species, concentration, duration, and route of ethanol administration (Choudhry et al, 2005;Kettunen et al, 1992;Mehta et al, 1998). Our results showed that 1dP/dt max was significantly reduced by the 5% concentration of ethanol.…”
Section: Discussionmentioning
confidence: 50%
“…In this latter study, spectral analyses presented evidence that ethanol caused remarkable shifts in the cardiac sympathovagal balance towards parasympathetic dominance, which resulted in weakening of the cardiac contractile force and lowered BP (El-Mas et al, 2011). These observations complement those of acute studies (El-Mas and Abdel-Rahman, 1999a; Choudhry et al, 2005), which highlighted a key role for reduced cardiac output in the ethanol-evoked hypotension (El-Mas and Abdel-Rahman, 1999a, 1999b). …”
Section: Introductionsupporting
confidence: 83%